Impact of Shari’ah Supervisory Board Diversity on the Performance of Islamic Banks: Evidence from Yemen Emerging Economy - Mohammed Sultan Saif, Gehad; Ika Sulistyawati, Ardiani; Karim, Abdul; Sista Devy, Happy (Journal International Economic Sharia, 2024)
Objective: This study aims to examine the correlation between the diversity of the Shari'ah Supervisory Board (SSB) and the financial performance of Islamic banks in Yemen. In particular, it studies how age, gender, nationality, education, tenure, size, and cross-membership influence bank performance.Methods: A quantitative research approachwas used based on panel data from a sample of Islamic banks in Yemen. Return on Assets (ROA), Return on Equity (ROE) and Operational Efficiency (OE) were used to measure financial performance. To assess the relationship between SSB diversity and performance, I performed a multiple regression analysis using bank size and market conditions as control variables.Results: The results show that age diversity, gender diversity, nationality diversity, and education background diversity positively contribute to Islamic banks' financial performance. Tenure diversity and cross-membership had no significant effects, though. These results underscore the need for diversity of skills and backgrounds in the Shari'ah Supervisory Board.Novelty: This study adds to the existing body of knowledge by offering empirical insights into the relationship between SSB diversity and financial performance in the context of Islamic banking, specifically focused on Yemen. All of these aspects of diversity offer various perspectives on how governance structures influence performance.Policy and Research Implications: Overall, the findings indicate that Islamic banks need to look into diversifying their Shari'ah Supervisory Boards to achieve better governance and financial performance. Further research could investigate the longevity and prevalence of diversity among SSBs and can also be extending this to other regions or also to other financial sectors.